Incidence of Neonatal Asphyxia Events In Mothers Maternity With Early Ruptured Amniotic Fluid - Albab, Muhamad Ulil; Widyaningsih, Heriyanti; Hartini, Sri; Ambarwati, Ambarwati (South East Asia Nursing Research, 2020)
Asphyxia and Intrauterine fetal dead (IUFD) are a threat if a premature rupture of membranes is not immediately treated quickly and appropriately. Neonatal asphyxia can occur due to complications from premature rupture of membranes. IMR in Indonesia is the fifth country for ASEAN countries, 35/1000 birth. Based on data from RA Kartini Hospital in Jepara, asphyxia cases from approximately (12,6%) and incidence of premature rupture of membranes 816 cases or around (85,8%). While the incidence of neonatal asphyxia born from PROM totalled 15 cases or about (1,6%).  This research using quantitative descriptive methods with cross-sectional design. This research was conducted on April 21-23, 2020 using a total sampling method of 148 respondents. The data used are secondary data with a single variable, namely the incidence of neonatal asphyxia in mothers with maternity premature rupture of membranes. Data analysis uses a descriptive statical test. Aims to know the description of the incidence of neonatal asphyxia in mothers with maternity premature rupture of membranes in General Hospital of Raden Ajeng Kartini Jepara 2019 and describe the incidence of neonatal asphyxia in mothers with maternity premature rupture of membranes in General Hospital Raden Ajeng Kartini Jepara 2019. The result showed that of 148 respondents on average had no risk age (20-35 years) as many as 120 respondents (81,1%) and the average parity PROM mothers as many as 148 respondents had multiparous parity of 85 respondents (57,4%). Then from 148 PROM mothers, 6 respondents (4,1%) gave birth to babies who had asphyxia. The highest incidence of neonatal asphyxia in mothers with maternity premature rupture of membranes was mild asphyxia of 3 respondents (2,0%), moderate to severe asphyxia of 2 respondents (1,4) and moderate asphyxia of 1 respondent (0,7%). The average degree of asphyxia in women with premature rupture of membranes is mild asphyxia.